Skate parks: a guide for landscape architects - Poirier, Desmond (Kansas State University, 2008)
Much like designing golf courses, designing and building skateboard parks requires very specific knowledge. This knowledge is difficult to obtain without firsthand experience of the sport in question. An understanding of how design details such as alignment, layout, surface, proportion, and radii of the curved surfaces impact the skateboarder's experience is essential and, without it, a poor park will result. Skateboarding is the fastest growing sport in the US, and new skate parks are being finished at a rate of about three per day. Cities and even small towns all across North America are committing themselves to embracing this sport and giving both younger and older participants a positive environment in which to enjoy it. In the interest of both the skateboarders who use them and the people that pay to have them built, it is imperative that these skate parks are built correctly. Landscape architects will increasingly be called upon to help build these public parks in conjunction with skate park design/builders. At present, the relationship between landscape architects and skate park design/builders is often strained due to the gaps in knowledge between the two professions. This does not have to be the case. This thesis synthesizes information about skate parks into design guidelines for landscape architects. This information comes from: 1. A case study of the Kansas City Skate Plaza (a.k.a. Penn Valley Skate Park), involving skating of the park, video/photography, physical measurements, and site analysis. 2. Books, articles, movies, and websites concerning ethnography, landscape architecture, concrete construction methods, skate park and pool construction methods,landscape architecture for public spaces, and skateboarding/ skateboarding culture. 3. Interviews with landscape architects, skate park design/builders, and skateboarders. The intent of this thesis is to help landscape architects familiarize themselves in preparation for working with the skate park design/builders.
Keywords: Skate parks; Skateboarding; Landscape architecture; Skateboards; Design guidelines; Architecture (0729); Recreation (0814); Urban and Regional Planning (0999)